ทัศนคติของสตรีต่อโฆษณาที่นำเสนอสตรีในบทบาทต่าง ๆ - อัมพิกา ศรีสุธาพรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
Studies: (1) females attitudes towards different female role portrayals in advertising, and (2) the relationship between females feminist consciousness and their attitudes towards advertising portraying different female roles. Survey method was used to collect data from 400 Bangkok females, aged 22-45 years old. By using the multi-stage sampling procedure, sampling districts were selected and the samples were conveniently chosen from the districts. The research instrument was a self-administered questionnaires. A series of 10 statements designed to assess feminine role orientation were also included in the questionnaires. Four types of female role portrayals were chosen for this study: (1) traditional portrayals, (2) non-traditional portrayals, (3) sex-object portrayals, and (4) superwoman portrayals. Frequency, percentage, mean scores and t-test were the statistics applied to analyze the data through SPSS Windows. Results are as follows: 1. Females with strong level of feminist consciousness have more favorable attitudes towards non-traditional role portrayals than the traditional ones. 2. Females with less level of feminist consciousness have more favorable attitudes towards traditional role portrayals than the non-traditional ones. 3. Females with less level of feminist consciousness have more favorable attitudes towards sex-object role portrayals in advertising compared to females with strong level of feminist consciousness.